Pharmacist’s Knowledge of Pulmonary Tuberculosis in a Cross Sectional Survey at Primary Health Care Centers in Surabaya, Indonesia - YUNI PRIYANDANI, - (Institute of Medico-Legal, 2019)
Objective: In Indonesia, tuberculosis (TB) cases rank third in the world. In 2017, East Java Province is ranked second with 48,323 total TB cases. Surabaya ranked first in East Java with 5,428 TB cases in 2016. Pharmacist could play an important role in antituberculosis drug therapy of TB patient. Pharmacist always begins to provide pharmaceutical care by making an assessment of the patient’s drug-related needs at the time. The pharmacist’s knowledge is fundamental to the implementation of pharmaceutical care. This study explored the TB-related knowledge of pharmacist at primary health care centers in Surabaya, Indonesia. Method: This cross-sectional study applied a questionnaire that was administered to a total of 63 pharmacists at primary health care centers in Surabaya, Indonesia. Data collection was carried out for 3 months from July to September 2018. The research instrument was in the form of questionnaire for pharmacists, consisting of questions on the characteristics of the diseases, drug characteristics, and patient characteristics knowledge. The data analysis using Statistical Product and Service Solutions (SPSS) version 18 for Windows. Results: The number of primary health care center pharmacists who did not perform pharmaceutical care was still high, ie. 37 (58.7%) from a total of 63 pharmacists. The knowledge of pharmacists regarding the characteristics of TB had the lowest value of 4.67 (46.67%) of the maximum value on the knowledge of antituberculosis drug characteristics and knowledge of patient characteristics. The topic of the question about the characteristics of TB includes the symptoms of tuberculosis, the classification of tuberculosis, the natural course of pulmonary tuberculosis, the nature of the acid-resistant bacilli, and the therapeutic response. Conclusion: The pharmacist’s knowledge regarding the characteristics of tuberculosis needs to be improved to support the pharmacist’s ability in pharmaceutical care for tuberculosis patients.